Dr. Erminio Mastroluca — Deep Plane Facelift — Milan - Mastroluca, Erminio (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Erminio Mastroluca, practicing in Milan, Italy. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003273; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; italy; milan